Analysis of the Effectiveness of Various Filtration Media in Clean Water Treatment: A Literature Review - Ni Wayan Mega Savira Utami (Physics Department, Faculty of Mathematics and Natural Sciences, Universitas Negeri Makassar, 2026)
Clean water treatment technology continues to develop in response to increasing water pollution problems caused by turbidity, organic pollutants, microorganisms, and dissolved contaminants. One of the most widely applied treatment methods is filtration using various media such as silica sand, activated carbon, zeolite, and biosand filters. This study aims to analyze the effectiveness of several filtration media in improving water quality based on previous research findings. The method used was a literature review with a descriptive analysis approach, examining ten scientific articles from national and international journals published between 2018 and 2025. The results indicate that silica sand is effective in reducing turbidity and suspended particles, activated carbon demonstrates strong adsorption capability for odor, color, and organic compounds, while zeolite effectively reduces heavy metals and ammonia through ion exchange mechanisms. Biosand filters show good performance in reducing microorganisms in household-scale water treatment. Furthermore, combinations of filtration media provide higher effectiveness than single media by simultaneously optimizing physical, chemical, and biological filtration processes. Therefore, selecting appropriate filtration media combinations is important to improve clean water treatment efficiency.